Constraints on Trenchward Arc Migration and Backarc Magmatism in the North Patagonian Andes in the Context of Nazca Plate Rollback - Fernández Paz, Lucía (2019)
Geochemical and geochronological data reveal that late Oligocene-early Miocene time is a break point in the evolution of Andean magmatism. The Patagonian Andes registered the onset of arc volcanism since the late Eocene forming part of the El Maitén Belt, whose development was driven by the subduction of the Farallon/Nazca plates beneath the Andean margin. During the Oligocene, the El Maitén Belt shows a change in the geochemical signature of its magmas from tholeiitic to calc-alkaline compositions, reflecting a more mature stage in the magmatic arc evolution. Toward the early Miocene, a striking event is registered in Andean volcanic sequences as mafic tholeiitic lava flows of the El Maitén are interbedded with marine deposits, suggesting their development in the context of a fast subsiding regime. Geochemical analyses presented in this paper show that these rocks resemble enriched mid-ocean ridge basalt-like and ocean island basalt compositions, isotopically depleted, which strongly contrast with previous arc products. By this time, a global plate reorganization event had caused an increase in convergence rates, accelerated rollback, and a more orthogonal geometry of subduction, triggering widespread magmatism and the development of extensional basins in the overriding plate. Arc-related volcanism during the early Miocene can be found only in the western slope of the Andes, suggesting the retreat of the volcanic front toward the trench. The proposed model highlights a strong linkage between the geochemical signature of magmatic products and changes in the subduction zone configuration and mantle dynamics during the evolution of the Patagonian Andes (41–44°S).